Upaya Peramalan Cadangan Minyak Pada Sumur SBR-A Menggunakan Metode Decline Curve Analysis - Sakinah; Firdaus; Joko Wiyono; Yudiaryono; Abdul Gafara Karim; Aliyah Sayyidina Putri Bahtiar; Darmiyati, Iin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
Oil and natural gas are needs that are needed by every country including Indonesia. national need. In the SBR-A well field R, this was used for final project research, namely estimating oil reserves using the decline curve analysis method, the SBR-A well experienced a decrease in production. The purpose of carrying out the decline curve analysis method is to estimate or predict the estimated ultimate recovery and oil production in the future, so that we can predict the future production prospects of the field under study, so that we can determine the best steps taken to develop the field. either in actual conditions or other conditions. Based on the research results obtained from data processing using the Decline Curve Method, it can be seen that the type of curve is Exponential decline, with an actual cumulative value of 51328.40203 STB and a decline exponential value (b) of 0.01 and a nominal value of decline (D) of 0.007. And the remaining oil reserves (ERR) up to the economic limit of 53865.62128 STB, so that the SBR-A well can produce up to the economic limit of 5 BOPD, which is 674 days or 1.9 years, which starts production from 8 May 2023 to 1 January 2025. With the value of the amount of reserves that can be produced (EUR) in the SBR-A Well, which is 105194,023 STB..